Comparative Analysis of Certain Requirements of Food Legislation in the European Union and the Customs Union of Russia, Belarus, and Kazakhstan - International Finance Corporation (World Bank Group, Washington, DC, 2015)
This report presents a comparative analysis of the food legislation requirements of the European Union (EU) and the Customs Union. Its purpose is to guide food business operators and public authorities engaged in reforming national food safety systems in the peculiarities of EU and Customs Union legal requirements and help them evaluate their capabilities in meeting those requirements. This report supports the International Finance Corporation’s efforts to facilitate the opening of new markets for the producers in emerging markets. This report compares the most critical aspects of food legislation of the EU and the Customs Union, such as: requirements and arrangements of food control; requirements to food quality; requirements to food labeling; food and food-related articles and materials that require special authorization; and laboratory control and food safety criteria. Ensuring food safety and consumer protection increasingly occupy the agendas of governments, which are looking to expand their trade networks. Likewise, food businesses interested in widening their export range need to understand quality and safety requirements in their target markets. This report offers unique, up-to-date information on the similarities and differences of the food safety requirements of the EU and Customs Union, with detailed assessments of the regulations that govern food safety.